Nanoelectrodes reveal the electrochemistry of single nickelhydroxide nanoparticles. Issue 11 (6th January 2016) - Clausmeyer, Jan; Masa, Justus; Ventosa, Edgar; Öhl, Dennis; Schuhmann, Wolfgang
Abstract : Individual Ni(OH)2 nanoparticles deposited on carbon nanoelectrodes are investigated in non-ensemble measurements with respect to their energy storage properties and electrocatalysis for the oxygen evolution reaction (OER). Abstract : Individual Ni(OH)2 nanoparticles deposited on carbon nanoelectrodes are investigated in non-ensemble measurements with respect to their energy storage properties and electrocatalysis for the oxygen evolution reaction (OER). Charging by oxidation of Ni(OH)2 is limited by the diffusion of protons into the particle bulk and the OER activity is independent of the particle size.